LATEST TECHNOLOGIES TO BE INTEGRATED IN TEACHING ENGLISH LANGUAGE - Rashidov, Sukhrob (Журнал иностранных языков и лингвистики, 2021)
Annotation. This paper tries to incorporate some of the technologies being used for teaching English language, course outcome and SWOT analysis. The new medium of communication as we all know, according to the NCTE Guidelines, English language “arts teachers should be sensitive to the needs of students, so that all students, regardless of differences, receive encouragement, support, and opportunities to learn". Keywords: Technology, Advancement, English, Learning, Integrating, Innovation.